Systemic lupus erythematosus with cardiorenal and neuropsychiatric involvement complicated by macrophage activation syndrome in a young female (Indian Journal of Case Reports, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder with highly variable presentations. Since no definitive diagnostic criteria exist, clinicians often rely on classification criteria to establish the diagnosis. A 22-year-old female presented to our hospital with a 2–3 month history of fever and weakness, along with breathlessness for 15 days. She had previously sought treatment at multiple peripheral centers, where only symptomatic therapy was provided, but no investigations were done till a few initial visits. At the time of presentation, clinical examination and investigations revealed neuropsychiatric symptoms, pancytopenia, pericardial effusion, renal involvement, and positive SLE serology. During hospitalization, she developed macrophage activation syndrome and multiorgan dysfunction. She was treated aggressively with high-dose corticosteroids, plasmapheresis, cyclophosphamide, dialysis, and mechanical ventilation. However, her condition rapidly deteriorated and progressed to a fatal outcome, which probably could have been prevented if the case had been investigated, diagnosed, and referred early. SLE flare is a highly fatal condition that can present abruptly. In view of this, prompt diagnosis and treatment of SLE is mandatory. Recommending specific diagnostic criteria and increasing awareness amongst the primary care physicians so that they also have a high index of suspicion for the condition in the presence of constitutional symptoms can reduce chances of missed diagnosis and reduce morbidity and mortality.